PENGARUH KARAKTERISTIK PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - HAPIDZ ALWI (Universitas Sarjanawiyata Tamansiswa, 2019)
ABSTRACTÂ The purpose of this study is to examine the effect of profitability, firm size, and leverage proxied into corporate characteristics, managerial ownership and institutional ownership proxied into good corporate governance towards corporate social responsibility disclosure. The dependent variable is disclosure of corporate social responsibility. Independent variables are profitability, company size, leverage, managerial ownership and institutional ownership. This study uses secondary data from annual reports and sustainability reports on Listed Companies in KOMPAS 100 on the Indonesia Stock Exchange in 2014-2017. Samples are 100 companies. This study uses a purposive sampling method and multiple linear regression as an analysis method. Before the regression test, it was tested using the classic assumption test. The results of this study indicate that company size and institutions do not have a significant effect on CSR disclosure while profitability, leverage, and managerial ownershipÂ